Development of Problem-Based Learning Strategies to Deepen Elementary School Students' Understanding of Social Studies Concepts - Hilma Innayah Putri; Keysha Kholillah Alqindy; Lisa Nabilah; Shafa Kamila Putri Anggraini; Nurdiansyah (COMPETITIVE: Journal of Education, 2025)
The discussion of this article focuses on the development of Problem-Based Learning (PBL) to improve students' understanding of social studies (IPS) concepts in elementary schools. This highlights the current challenges in IPS education, where students are often disinterested due to teaching methods that emphasize memorization rather than understanding. This discussion underscores the need for a shift towards PBL, which encourages students to think critically about real-world problems, thereby increasing their motivation and engagement in learning. PBL is recognized for its potential to improve students' critical thinking skills, learning outcomes, and process skills, which are essential for increasing their social awareness. This discussion also discusses the challenges and enabling factors in implementing PBL, emphasizing the importance of teacher training, project design, and the use of digital technology to facilitate student engagement. This article will summarize key points about the need for PBL in improving IPS learning, the challenges in its implementation, and strategies to overcome these challenges to improve student engagement and learning outcomes.